Enhanced particle fluxes and heterotrophic bacterial activities in Gulf of Mexico bottom waters following storm-induced sediment resuspension. (July 2016) - Ziervogel, K.; Dike, C.; Asper, V.; Montoya, J.; Battles, J.; D׳souza, N.; Passow, U.; Diercks, A.; Esch, M.; Joye, S.; Dewald, C.; Arnosti, C.
Abstract: Bottom nepheloid layers (BNLs) in the deep sea transport and remobilize considerable amounts of particulate matter, enhancing microbial cycling of organic matter in cold, deep water environments. We measured bacterial abundance, bacterial protein production, and activities of hydrolytic enzymes within and above a BNL that formed in the deep Mississippi Canyon, northern Gulf of Mexico, shortly after Hurricane Isaac had passed over the study area in late August 2012. The BNL was detected via beam attenuation in CTD casts over an area of at least 3.5 km 2, extending up to 200 m above the seafloor at a water depth of 1500 m. A large fraction of the suspended matter in the BNL consisted of resuspended sediments, as indicated by high levels of lithogenic material collected in near-bottom sediment traps shortly before the start of our sampling campaign. Observations of suspended particle abundance and sizes throughout the water column, using a combined camera-CTD system (marine snow camera, MSC), revealed the presence of macroaggregates (>1 mm in diameter) within the BNL, indicating resuspension of canyon sediments. A distinct bacterial response to enhanced particle concentrations within the BNL was evident from the observation that the highest enzymatic activities (peptidase, β-glucosidase) and protein production ( 3 H-leucine incorporation) were found within the most particle rich sections of the BNL. To investigate the effects of enhanced particle concentrations on bacterial activities in deep BNLs more directly, we conducted laboratory experiments with roller bottles filled with bottom water and amended with experimentally resuspended sediments from the study area. Macroaggregates formed within 1 day from resuspended sediments; by day 4 of the incubation bacterial cell numbers in treatments with resuspended sediments were more than twice as high as in those lacking sediment suspensions. Cell-specific enzymatic activities were also generally higher in the sediment-amended compared to the unamended treatments. The broader range and higher activities of polysaccharide hydrolases in the presence of resuspended sediments compared to the unamended water reflected enzymatic capabilities typical for benthic bacteria. Our data suggest that the formation of BNLs in the deep Gulf of Mexico can lead to transport of sedimentary organic matter into bottom waters, stimulating bacterial food web interactions. Such storm-induced resuspension may represent a possible mechanism for the redistribution of sedimented oil-fallout from the Deepwater Horizon spill in 2010.